Effect of light curing modes on the color stability of a nanohybrid composite immersed in different beverages = Efecto de diferentes modos de fotopolimerización en la estabilidad del color de una resina compuesta nanohíbrida inmersa en diferentes bebidas - Ozan, Gunce
Aim: Sufficient polymerization remains as crucial for composites to prevent discoloration. Both LEDs and halogen units are used for polymerization and different curing modes are improved to overcome inadequate polymerization. This in vitro study investigated staining susceptibility of a nano-hybrid resin composite light-cured in different modes and immersed in different staining media. Methods: Disc-shaped specimens were prepared from nano-hybrid resin composite (Filtek Z550) and light-cured according to following modes: Halojen (GI), LED standard (GII), LED pulse (GIII) or LED ramp (GIV). Half of the specimens of each group (n=7) were stored in one of the staining media (red wine or coffee) for 10 min/day during experimental period. Measurements were performed using spectrophotometer according to CIEL*a*b system at baseline and on 7, 28 and 56 days. Colour differences (∆E) between groups were submitted to statistical analysis. Results: Regarding 7-day evaluation, colour change values of specimens immersed in coffee revealed no remarkable difference among curing modes (p>0.05); whereas specimens in GIV were significantly less stained compared to specimens in GII and GIII when immersed in red wine. Regarding 56-days of evaluation, specimens of GIV showed statistically significant colour change in red wine compared to other groups. However specimens in GI revealed the least staining after 56-days of coffee immersion, and this result was statistically different from LED groups. Conclusion: This study suggest that light-curing mode influences the staining susceptibility of the tested composite. Composites polymerized with halogen unit showed lower staining than all LED modes. Despite novel light sources, halogen units may still used reliably at clinics.